Cultivation and evaluation of Pleurotus Sajor caju antimicrobial and phytochemical properties - SHARAD GOSWAMI; PRANITA GADHAVE (International Journal of Pharma and Bio Sciences, 2019)
Pleurotus sajor caju is an edible fungus commonly known as the oyster mushroom. In India it is popularly known as “Dhingari”. Present study focuses on cultivation Pleurotus sajor caju by solid state fermentation on paddy straw. Mushroom is a rich source of protein like soya , has vitamin B,C,D and also good source of iron, potassium and folic acid. Folic acid help to cure anemia. Phytochemical analysis of aqueous and methanol extracts of P. sajor caju to find out the presence of secondary metabolites, antimicrobial activity against Escherichia coli and Staphylococcus aureus by well diffusion method and the production of lab scale products like dried mushroom powder, mushroom soup, etc. P. sajor caju was successfully cultivated on 25th days spawn run till complete mycelia grow and harvesting. Phytochemical analysis of aqueous and ethanolic extract revealed the presence of phenol, alkaloids, proteins and carbohydrates. Antimicrobial activity was observed for aqueous extract against E.coli and S.aureus. and dried powder was prepared for the preparation of mushroom soup and other commercially valuable products. Wide range of applications from the mushroom fruit bodies and mycelium has attracted much attention in regard of nutritional components and secondary metabolites. A wide range of bioactive compounds along with a versatile production of extracellular enzymes on conducting the quantitative and qualitative phytocomponent tests were screened in Pleurotus sp., According to the results, Tannin, saponin, flavonoids were present in them. Preliminary phytochemical screening revealed the presence of varying quantities of alkaloids, flavanoids, saponins, tannins and steroids. These results therefore not only make these wild edible mushrooms popular to be consumed as good food source but may also be valuable in drug development.